Jornalismo e acesso à informação: a utilização da Lei de Acesso à Informação por jornalistas Paraibanos - Sousa, Verônica Maria Rufino de (2017)
This dissertation had the objective of analyzing the use of Law on Access to Information (LAI), Law No. 12,527 / 2011, by journalists from Paraíba, checking the possible changes that the legal device caused the public routines of these professionals. The Law came into effect on May 16, 2012, and represents, for the citizen, the possibility of greater participation in the public sphere, strengthening, consequently, democracy and encouraging accountability actions - that is, greater accountability by public managers. For journalists, the legal device is a instrument to obtain informations of public interest, which often tend to be hidden by the government. From a mapping of matters that cite the law, published in the newspapers: Correio da Paraiba and Jornal da Paraiba, in the first three years of its duration (that is, from May 2012 to May 2015), and the Interviews with the professionals of the mentioned newspapers, the following results were verified: the LAI approaches in the newspapers treat, strictly, of the interests of political managers from Paraiba; The main problems encountered by journalists in the use of the law refer to the incompatibility of the deadline for the return of the demands by the public agencies with the deadline of the drafting and the insufficiency of information made available. In this way, little has been used the law in the production of journalistic texts, and these professionals have preferably gone to the Press Office and the public manager to obtain information, that is, there were no significant changes in the productive routines of journalists working in the print media Of Paraiba.